Automated fitting of thermogravimetric analysis data. (22nd May 2020) - Bruns, Morgan C.; Leventon, Isaac T.
Summary: A novel methodology has been developed for extracting pyrolysis kinetic parameters from thermogravimetric analysis (TGA) data. The development of this methodology is motivated by a need to automate the determination of material properties for use in fire models. The algorithm with which the methodology is implemented is described. Aside from being fully automated, the resultant script has the advantage of being efficient—a full set of kinetic parameters is provided in less than 1 second. The script is verified against manufactured TGA data for one and two reaction mechanisms and the effects of reaction peak width and the distance between reaction peaks is examined. Validation is accomplished by applying the script to TGA data for Nylon 6, 6, a flexible polyurethane foam, and polyvinyl chloride. The resultant kinetic parameters are tabulated, and plots of the actual and predicted TGA data show that the algorithm is quite effective for one, two, and three reaction mechanisms.